Integrating Health and Safety in the Workplace. Issue 5 (May 2015) - Loeppke, Ronald R.; Hohn, Todd; Baase, Catherine; Bunn, William B.; Burton, Wayne N.; Eisenberg, Barry S.; Ennis, Trish; Fabius, Raymond; Hawkins, R. Jack; Hudson, T. Warner; Hymel, Pamela A.; Konicki, Doris; et al.
<x xml:space="preserve">Abstract</x> Objective: To better understand how integrating health and safety strategies in the workplace has evolved and establish a replicable, scalable framework for advancing the concept with a system of health and safety metrics, modeled after the Dow Jones Sustainability Index. Methods: Seven leading national and international programs aimed at creating a culture of health and safety in the workplace were compared and contrasted. Results: A list of forty variables was selected, making it clear there is a wide variety of approaches to integration of health and safety in the workplace. Conclusion: Depending on how well developed the culture of health and safety is within a company, there are unique routes to operationalize and institutionalize the integration of health and safety strategies to achieve measurable benefits to enhance the overall health and well-being of workers, their families, and the community.